The Influence of Competence and Organizational Culture on Employee Performance - Tjeri Hadjrillah; Amirudin Amirudin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
Research Objectives: This study aims to examine the influence of competence and organizational culture on employee performance at PT. Permata Graha Nusantara, West Jakarta. Specifically, the research objectives are: (1) to determine the effect of competence on employee performance, (2) to examine the impact of organizational culture on employee performance, and (3) to investigate the combined influence of competenc. Research Method: The study employs a quantitative descriptive research method. Data were collected using a structured questionnaire. The population consisted of 50 employees, and the sample was selected using a saturated sampling technique, which means that all 50 employees were included in the study. Data analysis was conducted through validity and reliability tests, classical assumption tests, multiple regression analysis, multiple correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. ResultsSimilarly, the t-test results for the organizational culture variable (X2) indicate that the calculated t-value (6.722) exceeds the critical t-value (2.011) and the significance level is below 5% (0.000), confirming that organizational culture significantly influences employee performance. The F-test results show that the calculated F-value (55.141) is greater than the critical F-value (2.80) at a 5% significance level (0.000 < 0.05), suggesting that competence and organizational culture together have a significant simultaneous effect on employee performance. Model Summary: The R Square value of 0.701 indicates that 70.1% of the variation in employee performance (Y) can be explained by competence (X1) and organizational culture (X2), while the remaining 29.9% is influenced by other factors not examined in this study.